2020
DOI: 10.1088/1741-4326/ab74a1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fast ions on a trapped-electron-mode dominated plasma in a JT-60U hybrid scenario

Abstract: The impact of fast ions on a trapped electron mode (TEM) is extensively analysed by linear and nonlinear gyrokinetic simulations for a JT-60U plasma at high β and low magnetic shear using the Gene code in local approximation. For the first time, it is shown that TEM-induced turbulent transport may remain unaffected by the steep fast ion pressure profile generated by the Neutral Beam Injection. Unlike recent observations of ion temperature gradient (ITG)-induced turbulent transport reductions due to fast ions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
(87 reference statements)
2
14
0
Order By: Relevance
“…These JET experimental observations are corroborated by modelling with the local (or 'flux-tube') version of the state-of-the-art gyrokinetic code GENE 36 that successfully reproduced turbulence properties for various tokamak experiments (see, for example, refs. 6,7,[37][38][39] ). For analysis of JET pulse #94701, we choose a flux tube around ρ tor = 0.23 (R = 3.25 m) as this region is characterized by large temperature gradients and a significant population of fast ions and TAEs.…”
Section: Numerical Modelling Of Turbulence Suppressionmentioning
confidence: 99%
“…These JET experimental observations are corroborated by modelling with the local (or 'flux-tube') version of the state-of-the-art gyrokinetic code GENE 36 that successfully reproduced turbulence properties for various tokamak experiments (see, for example, refs. 6,7,[37][38][39] ). For analysis of JET pulse #94701, we choose a flux tube around ρ tor = 0.23 (R = 3.25 m) as this region is characterized by large temperature gradients and a significant population of fast ions and TAEs.…”
Section: Numerical Modelling Of Turbulence Suppressionmentioning
confidence: 99%
“…α particles are also fast ions, thus are quite possible to affect the turbulent transport of helium ash. It has been indicated that fast ions can either stabilize or destabilize CTEM turbulence [33][34][35], depending on the type of free energy source and the regime of wavelength. However, the effects of α particles on the transport of helium ash driven by CTEM turbulence have not been further considered.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that TEM drives low-level transport of alpha particles 39 . The resonant interactions between energetic particles and micro-instability will be significant for ITG modes 40 , 41 but not for TEM and ETG modes because the propagation directions are opposite 42 . Therefore, interactions between energetic particles and TEM/ETG turbulence are expected to be weak.…”
Section: Discussionmentioning
confidence: 99%